THE EFFECTIVENESS OF USE OF DIFABLE RESIDENTIAL UNITS ON THE DESIGN OF A PROTOTYPE OF STUDENT FLATS FROM PUPR - Putri Yastine Nurlestya; Tutin Aryanti (Program Studi Arsitektur S-2 Universitas Pendidikan Indonesia, 2022)
Several universities in Indonesia have received assistance for the construction of student flats since the issuance of the policy on assistance for the construction of flats for higher education institutions. One of them is in the city of Bandung on the STAIPI Campus (Persistent Indonesian Islamic School of Religion) Bandung, Kec. Bojongsoang, Bandung City. This university received donations for a 1-tower student flat building with a prototype design. In this observation, we will discuss the effectiveness of the use of special housing units for the disabled in student flats, and that these disabled residential facilities are used properly according to their designation. The research methodology used is qualitative, and the research method used is a literature review method. In the 1 year, the student flats facilities, especially the disabled housing units, and several applications of inclusive designs have not been effective. For example, the disabled housing unit is temporarily filled by other students. The conclusion from the effectiveness of the use of special housing for the disabled is still not effective, because this student Rusunawa facility has only been operating for 1 year from the 2020 Academic Year to the 2021 Academic Year. Keywords: Student Flats, Disabled Residential Units, Prototype